Examining the Trend of Social Science Research on Urban Agriculture: A Bibliometric Review - Amira, Munifah Siti; Man, Norsida; Haris, Nur Bahiah; Ismail, Ismi Arif; Ahmi, Aidi; Maruf, Amar; Sulaiman, Winoryanti (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper aims to examine the current state of urban agriculture research under social science. This study used bibliometric analysis based on 424 documents obtained from the Scopus online database as of March 2021. Harzing’s Publish or Perish and VOSviewer software have been used to analyze and visualize the results. This article presents the findings based on the standard bibliometric indicators, with a focus on the rate of publication growth, citation analysis, and research productivity, documents and source type, the language of publications, subject area, most active source title, distributions of publications by countries, most dynamic institutions, authorship, keywords, title, and abstract analysis. The results indicate that urban agriculture literature has grown exponentially from 1984 until 2020. Simultaneously, the USA is ranked first in productivity, with 90 documents published (21.23%) by 1696 country analysis. Concerning citation frequency, with an average of 15 citations per year, the article published by [1] is the most quoted. Various studies on urban agriculture have been conducted using multi-authors and published in multiple languages by 21 authors from 41 different countries and 21 institutions.